Novel Cationic Meso-Arylporphyrins and Their Antiviral Activity against HSV-1 - Kseniya A. Zhdanova; Inga O. Savelyeva; Artem V. Ezhov; Andrey P. Zhdanov; Konstantin Yu. Zhizhin; Andrey F. Mironov; Natal'ya A. Bragina; Alla A. Babayants; Irina S. Frolova; Nadezhda I. Filippova; Nadezhda N. Scliankina; Olga N. Scheglovitova (MDPI AG, 2021)
This work is devoted to the search for new antiherpes simplex virus type 1 (HSV-1) drugs among synthetic tetrapyrroles and to an investigation of their antiviral properties under nonphotodynamic conditions. In this study, novel amphiphilic 5,10,15,20-tetrakis(4-(3-pyridyl-n-propanoyl)oxyphenyl)porphyrin tetrabromide (3a), 5,10,15,20-tetrakis(4-(6-pyridyl-n-hexanoyl)oxyphenyl)porphyrin tetrabromide (3b) and known 5,10,15,20-tetrakis(1-methyl-4-pyridinio)porphyrin tetraiodide (TMePyP) were synthesized, and their dark antiviral activity in vitro against HSV-1 was studied. The influence of porphyrin's nanosized delivery vehicles based on Pluronic F127 on anti-HSV-1 activity was estimated. All the received compounds 3a, 3b and TMePyP showed virucidal efficiency and had an effect on viral replication stages. The new compound 3b showed the highest antiviral activity, close to 100%, with the lowest concentration, while the maximum TMePyP activity was observed with a high concentration; porphyrin 3a was the least active. The inclusion of the synthesized compounds in Pluronic F-127 polymeric micelles had a noticeable effect on antiviral activity only at higher porphyrin concentrations. Action of the received compounds differs by influence on the early or later reproduction stages. While 3a and TMePyP acted on all stages of the viral replication cycle, porphyrin 3b inhibited viral replication during the early stages of infection. The resulting compounds are promising for the development of utilitarian antiviral agents and, possibly, medical antiviral drugs.